IMPLEMENTASI MEDIA INTERAKTIF WORDWALL DALAM LITERASI SAINS PADA MATA PELAJARAN IPAS SISWA KELAS IV SEKOLAH DASAR NEGERI MERTAN 1 - Putri Fedika Sari, Oney; Suswandari, Meidawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The purpose of this study was to describe the process of implementing the interactive media Wordwall in fostering scientific literacy in the IPAS subject for fourth-grade students at Mertan 1 Elementary School. The data collection techniques included observation, interviews, and documentation, involving 12 fourth-grade students as the research subjects. The data were analyzed using an interactive data analysis technique consisting of four stages: data collection, data reduction, data display, and conclusion drawing, processed using NVivo version 12. The findings revealed that the implementation of the interactive Wordwall media strengthened students’ scientific literacy concepts, including observing object images, classifying objects based on specific characteristics, and conducting real experiments such as changes in the states of matter using candles and ice cubes. Furthermore, students were able to identify the results of their observations and draw logical conclusions based on the facts obtained. The game-based features of Wordwall also created an enjoyable and challenging learning environment, fostering students’ interest, curiosity, and positive attitudes toward science that can be applied in their daily lives.